Productivity in Public sector : Concept of productivity in public sector and its difficulties - Kauppi, Perttu (My University, 2022)
Productivity is one of the most important concepts for economic growth. Productivity growth can be seen as enabling the development of the economy and society throughout modern histo-ry. At the same time, it has produced a lot of well-being for people. The importance of the con-cept of productivity cannot be overemphasized. But how is the concept of productivity understood in the public sector? What does the concept of productivity mean in the public sector in general? This thesis focuses precisely on these themes. The concept of productivity is usually understood in its original form. This refers to the economic productivity that describes the ratio between output and input. Concept of productivi-ty is also much more and includes several sub-concepts. Understanding the concept of productiv-ity is important so it can be studied in public sector. The aim of the thesis is to create a comprehensive summary of how the concept of productivity is applied in the public sector in Finland. The dissertation is implemented as a literature review. It combines previous studies and perspectives about the topic and creates conclusions. This thesis shows that the concept of productivity is not unambiguous in the public sector. In industrial and business world, productivity is measured with quantity of outputs, usually money. Public organizations do not seek for financial profit. This means outputs or “goods” are needed to define specific. This thesis also examines the measurement and development of productivity in the public sector. This thesis also represents a few public sector reforms aimed at improving productivity. An example of this is New Public Management, which effects on productivity have been contradictory.

Tuottavuus on yksi tärkeimmistä käsitteistä talouskasvun kannalta. Tuottavuuden kasvun voidaan nähdä mahdollistavan talouden ja yhteiskunnan kehityksen läpi historian. Samalla se on tuottanut ihmisille paljon hyvinvointia. Tuottavuuden käsitteen merkitystä ei voi selvästikään liikaa koros-taa. Mutta miten tuottavuuden käsite ymmärretään julkisella sektorilla? Mitä tuottavuuden käsitteellä tarkoitetaan julkisella sektorilla? Tämä opinnäytetyö keskittyy näihin teemoihin. Tuottavuuden käsite ymmärretään yleensä alkuperäisessä muodossaan. Tämä viittaa taloudelliseen tuottavuu-teen, joka kuvaa tuotannon ja panoksen välistä suhdetta. Tuottavuuden käsite on myös paljon enemmän ja sisältää useita alakäsitteitä. Tuottavuuden käsitteen ymmärtäminen on tärkeää, jotta sitä voidaan tutkia julkisen sektorin ympäristössä. Tämän opinnäytetyön tavoitteena on luoda kattava tiivistelmä tuottavuuden käsitteen sovelta-misesta julkisella sektorilla Suomessa. Tutkielma toteutetaan kirjallisuuskatsauksena ja se yhdis-tää aikaisempia tutkimuksia ja näkökulmia aiheeseen, sekä tuottaa johtopäätöksiä. Tämä tutkielma osoittaa, että tuottavuuden käsite ei ole julkisella sektorilla yksiselitteinen. Teol-lisuus- ja yritysmaailmassa tuottavuutta mitataan tuotoksen määrällä, yleensä rahalla. Julkiset organisaatiot eivät tavoittele taloudellista voittoa. Tämä tarkoittaa, että tuotokset täytyy määri-tellä erikseen. Tässä tutkielmassa tarkastellaan myös julkisen sektorin tuottavuuden mittaamista ja kehittämistä. Tutkielmassa käsitellään myös muutamia tuottavuuden parantamiseen tähtääviä julkisen sektorin uudistuksia. Esimerkkinä tästä on New Public Management -reformi, jonka vai-kutukset tuottavuuteen ovat olleet ristiriitaisia.
Keywords: public sector; public administration; productivity; efficiency (properties); Finland; public services; product development; fi=Julkisjohtaminen|en=Public Management|; fi=Hallintotieteiden maisteriohjelma|en=Master's Programme in Administrative Sciences|